1992
DOI: 10.1128/jb.174.23.7670-7679.1992
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a high-affinity iron transport system in Acinetobacter baumannii

Abstract: Analysis of a clinical isolate ofAcinetobacter baumannii showed that this bacterium was able to grow under iron-limiting conditions, using chemically defined growth media containing different iron chelators such as human transferrin, ethylenediaminedi-(o-hydroxyphenyl)acetic acid, nitrilotriacetic acid, and 2,2'-bipyridyl. This iron uptake-proficient phenotype was due to the synthesis and secretion of a catechol-type siderophore compound. Utilization bioassays using the SalmoneUla typhimurium iron uptake mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 75 publications
(54 reference statements)
4
41
0
Order By: Relevance
“…Smith et al (1990) detected the presence of iron chelator 2,3-dihidroxi-benzoic acid (DHBA) and IROMPS in the culture supernatant of Acinetobacter sp. Besides DHBA, A. baumannii strains present other siderophores type catechol (Echenique et al 1992, Actis et al 1993). The Fur protein of A. baumannii, which regulates the genes involved in iron uptake, was sequenced and indicated that it is 63% identical to that of E. coli (Daniel et al 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith et al (1990) detected the presence of iron chelator 2,3-dihidroxi-benzoic acid (DHBA) and IROMPS in the culture supernatant of Acinetobacter sp. Besides DHBA, A. baumannii strains present other siderophores type catechol (Echenique et al 1992, Actis et al 1993). The Fur protein of A. baumannii, which regulates the genes involved in iron uptake, was sequenced and indicated that it is 63% identical to that of E. coli (Daniel et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Growth under iron-limiting conditions -The isolates were grown on M9 minimal medium containing the iron chelator 2,2-dipyridyl (DIP) (Sigma) in concentrations of 50 µM and 200 µM and 2% agar (Echenique et al 1992). The plates were incubated at 37ºC for 18 h. DIP was prepared as a 20 mM stock solution in distilled water and kept at -20ºC.…”
Section: Bacterial Isolates -mentioning
confidence: 99%
“…This iron uptake system includes a catechol siderophore capable of scavenging iron from high-affinity iron-binding proteins present in the human host. Chemical analyses of a secreted catechol siderophore (14) and the absence of histamine in culture supernatants (3) indicate that the siderophore produced by this isolate is different from acinetobactin. This hypothesis is supported by the recent observation that a chromosomal region of this strain contains a gene cluster that includes a gene encoding a putative outer membrane siderophore receptor protein unrelated to the V. anguillarum and A. baumannii 19606 FatA and FatA-like proteins, respectively (13).…”
mentioning
confidence: 99%
“…A previous report characterized a high-affinity iron uptake system expressed by A. baumannii 8399, which was isolated during a nosocomial outbreak of respiratory infections at the Oregon Health Sciences University Hospital, Portland (14). This iron uptake system includes a catechol siderophore capable of scavenging iron from high-affinity iron-binding proteins present in the human host.…”
mentioning
confidence: 99%
“…The production of siderophores is one strategy used by the pathogen to grow under ironlimiting conditions (56,57). Siderophores are small secreted molecules that bind iron with high affinity and can be taken up by bacteria as a way to scavenge trace iron from their surroundings.…”
Section: Iron Acquisitionmentioning
confidence: 99%